Pachydermoperiostosis ('Touraine-Solente-Gole' Syndrome) - Sharma, R; Pandey, S; Choudhary, D; Pokhrel, DB (Nepal Journal of Dermatology, Venereology & Leprology, 2013)
DOI: http://dx.doi.org/10.3126/njdvl.v11i1.7937 Nepal Journal of Dermatology, Venereology & Leprology Vol.11(1) 2013 pp.64-68